Fatal giant pediatric intracranial cavernous angioma - Corapçioğlu, Funda; Akansel, Gür; Gönüllü, Erdem; Yildiz, Kürşat; Etuş, Volkan (The Turkish Journal of Pediatrics, 2006)
Cavernous angioma is a benign vascular lesion that may occur in the central nervous system. The symptoms of raised intracranial pressure or consciousness alteration are usually related to acute hemorrhage. A previously healthy four-year-old girl was admitted with sudden loss of consciousness, vomiting and clonic seizures. Her Glasgow coma score (GCS) was 7 at presentation (5 m 1v 1e). Anisocoria and mydriasis were present on the right. Computerized tomography revealed a giant spherical, hyperdense intraaxial left frontoparietal lesion. The findings of surrounding vasogenic edema and compression of the adjacent lateral ventricle were seen on computerized tomography (CT). She was taken to operation and the mass was grossly excised. The GCS remained unchanged. A diagnosis of brain death was made. A cavernous hemangioma was diagnosed with pathologic examination. In conclusion, a cavernous angioma may occasionally follow a rapid and fatal course by causing gross hemorrhage in the pediatric age group. Early recognition by CT or magnetic resonance imaging (MRI) and prompt surgical evacuation are necessary.